2001
DOI: 10.1021/bi015848u
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Substrate Distortion and Intramolecular Hydrogen Bonding in Enzymatic Catalysis by Scytalone Dehydratase

Abstract: Alternative substrates and site-directed mutations of active-site residues are used to probe factors controlling the catalytic efficacy of scytalone dehydratase. In the E1cb-like, syn-elimination reactions catalyzed, efficient catalysis requires distortion of the substrate ring system to facilitate proton abstraction from its C2 methylene and elimination of its C3 hydroxyl group. Theoretical calculations indicate that such distortions are more readily achieved in the substrate 2,3-dihydro-2,5-dihydroxy-4H-benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Therefore, it is important to recognize the role played by the HB in stabilizing radicals and the anionic species in phenols, for example, in acylphloroglucinols [ 32 , 33 ]. Usinic acid [ 34 ] produced by lichens acts as an effective antibiotic and scytalone dehydratase is crucial for the fungal melanin biosynthetic pathway [ 35 ]. Some quinones (lapachol, caryopteron) [ 36 ] exhibit important cytotoxic activity against cancer cells, naphthazarin [ 37 ] acts as an antibacterial agent, apoptosis inducer, antineoplastic agent, and the most common application of anthraquinones remains the dyeing of both natural and synthetic fibres [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to recognize the role played by the HB in stabilizing radicals and the anionic species in phenols, for example, in acylphloroglucinols [ 32 , 33 ]. Usinic acid [ 34 ] produced by lichens acts as an effective antibiotic and scytalone dehydratase is crucial for the fungal melanin biosynthetic pathway [ 35 ]. Some quinones (lapachol, caryopteron) [ 36 ] exhibit important cytotoxic activity against cancer cells, naphthazarin [ 37 ] acts as an antibacterial agent, apoptosis inducer, antineoplastic agent, and the most common application of anthraquinones remains the dyeing of both natural and synthetic fibres [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In combination with site-directed mutagenesis, substrates with different physical properties, relevant to the reaction coordinate, are generally useful in pinpointing roles of native amino acid residues in stabilizing different aspects of the reaction's transition state. This strategy was first applied to identify active-site residues involved in distorting substrate ring conformations to their transition-state geometries mandated by stereoelectronic principles in the case of scytalone dehydratase acting on scytalone and the more easily deformed alternate substrate 2,3-dihydro-2,5-dihydroxy-4H-benzopyran-4-one [21]. The strategy was first applied to glycoside hydrolases in the case of SXA acting on 4NPX and 4NPA [11].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, our results indicated that only incorporation of PKS, SCD, and THR cloned from A. alternata into the genome of M. anisopliae allowed proper function by promoting the synthesis of the desired DHN melanins. This makes sense based on the recent enzymatic kinetic and protein crystallographic studies on two naphthol reductases (4HNR and 3HNR) and SCD (32,56,64). The two enzymes 4HNR and 3HNR have been shown to catalyze the reactions of two physiological substrates, 1,3,6,8-THN and 1,38-THN, but the substrate preferences and K cat /K m ratios vary (32,56).…”
Section: Discussionmentioning
confidence: 99%
“…The two enzymes 4HNR and 3HNR have been shown to catalyze the reactions of two physiological substrates, 1,3,6,8-THN and 1,38-THN, but the substrate preferences and K cat /K m ratios vary (32,56). Likewise, the capability of SCD to catalyze the reaction of the two physiological substrates, scytalone and vermelone, has been unequivocally proven (64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation